An Apocalypse Converted: William Stringfellow and Catholic Social Teaching on Climate Breakdown. (November 2021) - Hargaden, Kevin
In Laudato Si', Pope Francis advances the concept of integral ecology to connect the environmental crisis with a range of social crises afflicting our societies. This concept is grounded in a theological commitment, but directed towards its political effects. Those two trajectories are represented by the encyclical's articulation of a spiritual awakening described as an ecological conversion and its repeated calls to dialogue. Francis is not unaware of the risk that a naïve engagement in dialogue could stifle serious mitigation of the crises we face. Yet, even with many dire warnings about outcomes, much of the contemporary discourse around the climate and biodiversity crisis runs the risk of underestimating the nature of the problem. Apocalyptic theology, specifically in the work of William Stringfellow, is proposed as a valuable interlocutor at this point. Stringfellow's account of the Christian life as a battle with the forces of Death allows Christians to name that which we are converted from in an ecological conversion, strengthening the grounds upon which dialogue is engaged.